Air stable n-doping of WSe2 by silicon nitride thin films with tunable fixed charge density - Kevin Chen; Daisuke Kiriya; Mark Hettick; Mahmut Tosun; Tae-Jun Ha; Surabhi Rao Madhvapathy; Sujay Desai; Angada Sachid; Ali Javey (APL Materials, 2014)
Stable n-doping of WSe2 using thin films of SiNx deposited on the surface via plasma-enhanced chemical vapor deposition is presented. Positive fixed charge centers inside SiNx act to dope WSe2 thin flakes n-type via field-induced effect. The electron concentration in WSe2 can be well controlled up to the degenerate limit by simply adjusting the stoichiometry of the SiNx through deposition process parameters. For the high doping limit, the Schottky barrier width at the metal/WSe2 junction is significantly thinned, allowing for efficient electron injection via tunneling. Using this doping scheme, we demonstrate air-stable WSe2 n-MOSFETs with a mobility of ∼70 cm2/V s.